Intuition or experience? Tacit knowledge in decision making - Klein, Gary (Henry Stewart Talks, 2018)
This case study examines the intuition and tacit knowledge of nurses in a neonatal intensive care centre. In the late 1980s, nurses in an American neonatal intensive care centre could accurately diagnose sepsis in infants before receiving the results of the blood tests.
Archived at 2023/06/22